Essential Oils Oils of Nature - El-Shemy, Hany A. (IntechOpen, 2020)
Essential oils were used globally as a folk medicine for the treatment of a number of diseases because of the high content of natural compounds. Therefore, this book looks at research topics dealing with isolation, purification, and identification of active ingredients of essential oils from plants. This knowledge will provide significant information about essential oils to researchers and others interested in the field.